KEARIFAN LOKAL POMA AADUHUNUDI DESA SOAMAETEK KECAMATAN KAO BARAT KABUPATEN HALMAHERA UTARA - Nelci Balisosa; Vicky Richard Bernhard Moniaga; Sherly Gladys Jocom (AGRI-SOSIOEKONOMI, 2020)
This study aims to describe the local wisdom of â€œPoma Aaduhunuâ€ that occurs in Soamaetek Village,Â Kao Barat District, North Halmahera Regency in terms of the cultural aspects of cooperation in the field ofÂ coconut farming, marriage culture, the culture of building a house or place of residence. This research wasÂ conducted from June to August 2019. Respondent was selected used purposive sampling method. This study usedÂ primary data and secondary data. Primary data were obtained from interviews, based on a list of questions thatÂ had been provided in the form of a questionnaire, with 20 household heads (KK) as respondents, who came fromÂ community members in Soamaetek Village. Secondary data were obtained from the village office and the officesof agencies related to the research. Data analysis using descriptive analysis method, the data is presented inÂ tabular form and described descriptively. The results showed that the local wisdom of â€œPoma Aaduhunuâ€ inÂ Soamaetek Village, Kao Barat District, North Halmahera Regency is cooperation or mutual assistance which isÂ still very strong in practice, namely in the field of coconut farming in land preparation and harvesting; theÂ culture of the marriage at the marriage proposal ceremony (â€œmaso mintaâ€), making the â€œsabuaâ€ at the venue,Â preparing consumption for the wedding ceremony; house construction on land preparation and house buildingÂ process. The people of Soamaetek Village still adhere to this local wisdom because they consider the localwisdom culture of â€œPoma Aaduhunuâ€ to be very helpful in their daily lives.â€ Poma Aaduhunu'sâ€ local wisdomÂ has taken root and has become a culture inherent that has been passed down from generation to generation inÂ the Soamaetek Village community.*eprm*